2018
DOI: 10.1177/1177271918792246
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Measurements for Diagnosing and Characterizing Leukemoid Reactions and Immunohistochemical Validation of a Granulocyte Colony-Stimulating Factor and CXCL8-Producing Renal Cell Carcinoma

Abstract: Background:Various paraneoplastic syndromes are encountered in renal cell carcinomas. This case report illustrates that a paraneoplastic leukemoid reaction may precede the diagnosis of renal cell carcinoma and be explained by cytokine production from the cancer cells.Case presentations:A 64-year-old man was referred for hematology workup due to pronounced leukocytosis. While being evaluated for a possible hematologic malignancy as the cause, he was found to have a metastasized renal cell carcinoma, and hyperle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Combined with the survival analysis ( http://gepia.cancer-pku.cn/index.html ), 11 genes exhibited significant clinical outcome and accorded with the malignancy of the genes. Among the 11 significant DEGs, 4 genes, such as AIM2, 14 IGF2BP3, 15 CXCL13 16 and IL20RB 17 had been demonstrated to play critical roles related to the development of RCC. The other 7 genes had not been reported to be associated with RCC growth and progression.…”
Section: Resultsmentioning
confidence: 99%
“…Combined with the survival analysis ( http://gepia.cancer-pku.cn/index.html ), 11 genes exhibited significant clinical outcome and accorded with the malignancy of the genes. Among the 11 significant DEGs, 4 genes, such as AIM2, 14 IGF2BP3, 15 CXCL13 16 and IL20RB 17 had been demonstrated to play critical roles related to the development of RCC. The other 7 genes had not been reported to be associated with RCC growth and progression.…”
Section: Resultsmentioning
confidence: 99%
“…While having stringent DE analysis (DEseq; FDR < 0.05, fold change > 2), we revealed a higher number of upregulated (n = 148) compared with downregulated genes (n = 46) under the expression of VHL-S65P, and upregulated (n = 248) compared with downregulated genes (n = 142) under the expression of VHL-S65W, suggestive of gain of function mutations in VHL stabilizing HIF2α. Among the most altered genes, it has been shown that renal cancer progression can be promoted by upregulation of CXCL8 [ 23 ], ADAM9 [ 24 ], NDRG1 [ 25 ], SOD2 [ 26 ], SREBF1 and SREBF2 genes [ 27 ]. The genes NDRG1 [ 25 ] and SREBF2 [ 27 ] have also been reported as potential prognostic biomarkers for RCC, and SREBF1/2 were found to play roles in regulating lipid metabolism and have effects on ccRCC growth and survival.…”
Section: Resultsmentioning
confidence: 99%
“…Two retrospective studies have shown that most leukemoid reactions are caused by solid tumours, 3 , 4 and the abnormal increase in WBC count may be caused by abnormal secretion by tumour cells. 5 Other non-tumour causes include infection, a side-effect of corticosteroid treatment or haematopoietic growth factors, severe haemorrhage, and bone metastases with necrosis. In clinical settings, a common dilemma has been the differential diagnosis between tumour and infection.…”
Section: Discussionmentioning
confidence: 99%